Strategi Pendidikan Agama Kristen Mengatasi Pembulian Online dan Implikasinya terhadap Kesehatan Mental Pemuda - Remegises Danial Yohanis Pandie; Romika (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
The purpose of this study is to explain the strategy of Christian Religious Education in overcoming the phenomenon of online bullying experienced by young people. On the other hand, Christian religious education has not realized the effects of online bullying on the mental damage of Christian youth. This happens because Christian religious education focuses more on things that are visible to the naked eye, so that it ignores things that happen in cyberspace. The method used is a literature study. The results of the study show that Christian religious education has a strategy to overcome the problem of online bullying through teachers, churches and families. Preparation of appropriate strategies is an alternative that needs to be prepared by schools, churches and families so that young people who experience online bullying feel safe and healthy and know how to deal with online bullying.